Mechanism of action of GABA B receptor in anterior pituitary cells: Mechanism of action coupled to endocrine effects - Lux, Victoria Adela R. (2001)
The activation of pituitary GABA(B) receptors by the specific agonist baclofen inhibits pituitary hormone secretion in vitro. Here we studied the mechanism of action of GABA(B) receptors in rat adenohypophysis. Anterior pituitary cells were obtained by trypsinization and were either plated for hormonal studies and cAMP determination or incubated in FURA 2AM for calcium measurements. Baclofen (BACL: 1 x 10(-5) M) significantly inhibited basal and thyrotropic releasing hormone (TRH)-stimulated (1 x 10(-7) M) PRL secretion in anterior pituitary cells from proestrous rats. In the presence of pertussis toxin (PTX: 150 ng/ml, 20 h), which leads to the uncoupling of the G(i/o)-protein from the receptor, both effects of BACL were abolished while the effect of dopamine (DA: 1 x 10(-8) M), used as an inhibitory control, was reduced from 70 to 25%. PTX also reversed BACL-induced inhibition of gonadotropin-releasing hormone (GnRH)-elicited luteinizing hormone (LH) secretion in anterior pituitary cells from 15-day-old female rats. In addition, though working in a pituitary mixed cell population, in which only some cell types possess GABA(B) receptors, BACL (1 x 10(-5) M) attenuated the forskolin-induced (0.5 microM) increase in cAMP. This effect was prevented by co-incubation with the antagonist 2 hydroxysaclofen and by preincubation with PTX. BACL (5 x 10(-5) M) and DA (5 x 10(-7) M) inhibited basal intracellular calcium concentrations ([Ca(2+)](i)) in pituitary cells and the effect of the latter was significantly stronger. The effect of BACL on [Ca(2+)](i) was abolished after preincubation with PTX. In the presence of the potassium channel blocking agents barium (200 microM and 1 mM) and tetraethylammonium (10 mM), BACL was still able to inhibit [Ca(2+)](i). Blockade of voltage-sensitive calcium channels (VSCC) with either verapamil (5 x 10(-6) M) or nifedipine (1 x 10(-6) M) completely abolished the effect of BACL on [Ca(2+)](i). In the presence of 12.5 mM potassium concentration baclofen significantly inhibited [Ca(2+)](i). In conclusion, our results describe the negative coupling of adenohypophyseal GABA(B) receptors to VSCC through PTX-sensitive G-proteins. These characteristics suggest a resemblance of these receptors to the typical presynaptic GABA(B) sites described in the central nervous system.